Solving the mystery of the internal structure of casein micelles. Issue 14 (14th April 2015) - Ingham, B.; Erlangga, G. D.; Smialowska, A.; Kirby, N. M.; Wang, C.; Matia-Merino, L.; Haverkamp, R. G.; Carr, A. J.
<x xml:space="preserve">Abstract</x> Resonant soft X-ray scattering identifies key scattering features of casein micelles (after de Kruif et al. 2012).